2019
DOI: 10.1016/j.omtm.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Immunology of Adenoviral Vectors in Cancer Therapy

Abstract: Adenoviruses are a commonly utilized virus for gene therapy platforms worldwide. Since adenovirus components are characterized as highly immunogenic, their immunogenicity inhibits the widespread use of adenoviral vectors to treat genetic disorders. However, stimulation of the immune response can be exploited for cancer immunotherapy platforms, and thus adenoviral vectors are used for therapeutic gene transfer, vaccines, and oncolytic agents in the cancer gene therapy field. It is now accepted that the generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 107 publications
(117 reference statements)
1
62
0
Order By: Relevance
“…AdV vectors are a commonly utilized delivery vector in mouse models; they are ideal for delivery of the entire CRISPR/Cas9 system in one vector, with high transfection efficacy and they limit potential off-target effects because their genome does not integrate into the host genome 46 48 . Although the initially encountered high immunogenicity inhibited their widespread use to treat genetic disorders, the overall picture changed when it was recognized that adenoviral infection in a tumor can activate a robust immunogenic response, creating new opportunities in cancer therapy 49 , 50 . The number of clinical trials using oncolytic AdVs is increasing, and at present more than 32 trials are underway in different phases ( https://clinicaltrials.gov ) 51 .…”
Section: Discussionmentioning
confidence: 99%
“…AdV vectors are a commonly utilized delivery vector in mouse models; they are ideal for delivery of the entire CRISPR/Cas9 system in one vector, with high transfection efficacy and they limit potential off-target effects because their genome does not integrate into the host genome 46 48 . Although the initially encountered high immunogenicity inhibited their widespread use to treat genetic disorders, the overall picture changed when it was recognized that adenoviral infection in a tumor can activate a robust immunogenic response, creating new opportunities in cancer therapy 49 , 50 . The number of clinical trials using oncolytic AdVs is increasing, and at present more than 32 trials are underway in different phases ( https://clinicaltrials.gov ) 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the PEGylation of CCMV capsids (CCMV-PEG) greatly reduced the immunogenic response, BMV seems to be a better nanocarrier candidate due to its low immunological response. On the other hand, and despite of the immunogenicity of CCMV, which can limit its use for certain therapies, this virus could act as an immunoregulator in immunological therapies to improve some cancer treatments [47,48].…”
Section: Immunogenicity Of Ccmv and Bmvmentioning
confidence: 99%
“…As previously mentioned, many studies evaluating OAds have successfully shown targeted tumor cell lysis in pre-clinical models, both in vitro and in vivo, but have limited therapeutic efficacy in clinical trials. The immunology of Ad vectors in cancer gene therapy was recently reviewed and addresses how critical the anti-adenoviral and anti-tumor responses are for the efficacy of adenovirotherapies against cancer [73]. The field has made great progress in developing more relevant 3D in vitro models, but to fully test the efficacy and mechanisms of OAd therapy, in vivo models are required to measure the immune response to OAds.…”
Section: In Vivo Modeling Of Oncolytic Adenovirusesmentioning
confidence: 99%
“…Generally, to create these models immunodeficient mice are injected with human cells, tissues, or stem cells that reconstitute in these animals a human immune system [88]. The development of any humanized mouse is complex, time consuming, and expensive compared to xenograft models, but they provide a unique environment to test OAd replication in human tumors and the ability to study human immune responses in vivo [73].…”
Section: Humanized Mouse Models For Oad Therapiesmentioning
confidence: 99%